Analisis Faktor-Faktor Penyebab Piutang Tak Tertagih dan Upaya Penanggulangan serta Penyelesaian Piutang Tak Tertagih - Septiandra Loviriani; Lili Syafitri; Aris Munandar (Journal of Economics and Management Scienties, 2023)
CV. Jakaharta Palembang is a household equipment distributor company which in its business activities sells products, such as: stella, hit, mitu, elephant stamp mouse glue, fogo, proclin, carrera sponge and others. The payment system for purchasing goods at CV. Jakarta Palembang can be done in cash or credit. The sale of a credit system will result in receivables and uncollectible accounts. As for the purpose of this study is to determine the factors that cause uncollectible accounts and efforts to overcome and settle uncollectible accounts at CV. Jakarta, Palembang. The following are the results of research on the factors that cause uncollectible accounts at CV. Jakarta Palembang comes from internal parties and external parties. From internal parties, such as: not yet implementing a payment system in installments or in installments, grouping based on age of receivables and weak collection techniques have not been applied. While external factors, such as: bad character, declining financial conditions and failure of the business they operate. Efforts to deal with uncollectible accounts that have been carried out by CV. Jakaharta Palembang by visiting shops, looking for solutions and writing warning letters. While efforts to settle uncollectible accounts that have been carried out by CV. Jakaharta Palembang by rescheduling and reconditioning. For future research it is suggested to be able to reduce uncollectible accounts above 3% on CV. Jakaharta Palembang, can be done by implementing payment in installments, employing a debcollector and giving a discount to pay off the receivables